Influence of biochemical composition during hydrothermal liquefaction of algae on product yields and fuel properties. (November 2017) - Shakya, Rajdeep; Adhikari, Sushil; Mahadevan, Ravishankar; Shanmugam, Saravanan R.; Nam, Hyungseok; Hassan, El Barbary; Dempster, Thomas A.
Graphical abstract: Highlights: Hydrothermal liquefaction of nine algae species was performed. The regression model for bio-oil yield obtained was developed. The highest amounts of bio-oil yield was obtained from high lipid containing algae. Bio-oil yield showed the trend of lipid > protein > carbohydrate. Almost 50% of bio-oil was in vacuum gas oil range in most cases. Abstract: Hydrothermal liquefaction (HTL) of nine algae species were performed at two reaction temperatures (280 and 320 °C) to compare the effect of their biomass composition on product yields and properties. Results obtained after HTL indicate large variations in terms of bio-oil yields and its properties. The maximum bio-oil yield (66 wt%) was obtained at 320 °C with a high lipid containing algae Nannochloropsis . The higher heating value of bio-oils ranged from 31 to 36 MJ/kg and around 50% of the bio-oils was in the vacuum gas oil range while high lipid containing algae Nannochloropsis contained a significant portion (33–42%) in the diesel range. A predictive relationship between bio-oil yields and biochemical compositions was developed and showed a broad agreement between predictive and experimental yields. The aqueous phases obtained had high amount of TOC (12–43 g/L), COD (35–160 g/L), TN (1–18 g/L), ammonium (0.34–12 g/L) and phosphate (0.7–12 g/L).